A pixelated frequency-agile metasurface for broadband terahertz molecular fingerprint sensing. Issue 27 (20th June 2022) - Sun, Lang; Xu, Lei; Wang, Jiayi; Jiao, Yanan; Ma, Zenghong; Ma, Zhaofu; Chang, Chao; Yang, Xiao; Wang, Ride
Abstract : An ultra-broadband THz fingerprint metasensor is realized by introducing a pixelated frequency-agile metasurface assembling a one-to-many mapping between spatial and spectral information, paving the way to miniaturizing device footprints. Abstract : Terahertz (THz) plasmonic resonance based on an arbitrarily designed resonance metasurface is the key technique of choice for enhancing fingerprint absorption spectroscopy identification of biomolecules. Here, we report a broadband THz micro-photonics sensor based on a pixelated frequency-agile metasurface and illustrate its application ability to enhance and differentiate the detection of broadband absorption fingerprint spectra. The design uses symmetrical metal C-shape resonators with the functional graphene micro-ribbons selectively patterned into the gaps. A strong electric resonance with a high quality factor was formed, consisting of an electric dipole mode associated with the excitation of a dark toroidal dipole (TD) mode through the coupling from the electric dipole moment of the individual frequency-agile meta-unit. The resonance positions are nearly linearly modulated with the varying Fermi level of graphene. The configuration arranges a certain metapixel of the metasurface to multiple response spectra assembling a one-to-many mapping between spatial and spectral information which is instrumental in greatly shrinking the actual size of the sensor. By the synchronous regulation of graphene and C-shape rings, we have obtained highly surface-sensitive resonances over a wide spectral range (∼1.5 THz) with a spectral resolution less than 20 GHz. The target multiple enhanced absorption spectrum of glucose molecules is read out in a broadband region with high sensitivity. More importantly, the design can be extended to cover a larger spectral region by altering the range of geometrical parameters. Our microphotonic technique can resolve absorption fingerprints without the need for spectrometry and frequency scanning, thereby providing an approach for highly sensitive and versatile miniaturized THz spectroscopy devices.